(untitled) (مجلة الواحات للبحوث والدراسات, 2023)
ملخص: هذه دراسة وصفية استقرائية تهدف إلى الكشف عن منهج (التأويل) عند المفسر (محمد الطاهر بن عاشور) في تفسيره (التحرير والتنوير)، تقدم تحليلا لرؤيته لمفهوم (التأويل) وقضاياه الجدلية في مدارس التفسير الإسلامية، وللآليات والأدوات الإجرائية التي وظّفها في تفسير (القرآن الكريم). وقد رافق الوصف والاستقراء مقارنات بين تأويلية "ابن عاشور" وغيره من مدارس التأويل قديما وحديثا، في التراث الإسلامي، وفي المناهج الغربية، إذ أبرزت المقارنة موقفه وموقعه من التجربة الإنسانية العامة. كلمات دالة: تأويل – تحرير وتنوير - الطاهر بن عاشور – قرآن. Abstract: This is an inductive-descriptive study that attempts to reveal the interpreter Muhammad al-Tahir ibn Ashur’s interpretation approach to “Ta’aweel” (interpretation) in his Qur’anic exegesis " Al-Tahrir wa’l-tanwir" . The study provides an analysis on his visions about the concept of " Ta’weel" and its controversial issues in the islamic schools of interpretation. We’ll also study the mechanisms and the procedural tools that he had used in his interpretation of the Holy Qur’an. The description and the induction in this study is accompanied with a comparison between the interpretations of Ibn ’Ashur with older and modern schools of interpretation from the Islamic heritage and the western curriculum. This comparison highlighted his point of view about human experience. Key words: Interprètation - al-tahir ibn Ashur - Al-Tahrir wa’ltanwir – Quran